2022
DOI: 10.1037/sah0000320
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diagnostic label construction and gender on stigma about borderline personality disorder.

Abstract: Borderline personality disorder (BPD) is highly stigmatized. Although person-first labels are now used for most mental illnesses (e.g., a person with schizophrenia) rather than premodified noun labels (e.g., "he is a schizophrenic"), it is still common to hear people referred to as "borderlines." In a series of two experimental studies, we examined how diagnostic labels influence negative attitudes about BPD. In Study 1, we presented vignettes with no diagnostic label, a person-first label, or a premodified no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 70 publications
(104 reference statements)
2
14
1
Order By: Relevance
“…The vlogs were destigmatizing, informing and educating others on BPD, a disorder that is highly stigmatized and misunderstood ( Cone, 2020 ; Kirtley et al, 2019 ; Masland and Null, 2021 ; Zimmerman et al, 2015 ). Researchers Thomas et al (2015) have highlighted the need for further research into the utilization of online interventions in reducing stigma – and self-stigma – for those suffering with mental health issues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The vlogs were destigmatizing, informing and educating others on BPD, a disorder that is highly stigmatized and misunderstood ( Cone, 2020 ; Kirtley et al, 2019 ; Masland and Null, 2021 ; Zimmerman et al, 2015 ). Researchers Thomas et al (2015) have highlighted the need for further research into the utilization of online interventions in reducing stigma – and self-stigma – for those suffering with mental health issues.…”
Section: Discussionmentioning
confidence: 99%
“…Even though there are more females than males with BPD ( APA, 2013 ), males can also receive a BPD diagnosis. There is also evidence that females may experience the disorder differently to their male counterparts ( Álvarez-Tomás et al, 2019 ; Masland and Null, 2021 ). Therefore, male vloggers may have given voice to a different perspective and, as such, elicited different comments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, because person-first language in practice is typically restricted to conditions that are stigmatized, such efforts may backfire and unintentionally accentuate stigma rather than reduce it ( 43 ). While previous literature has suggested an association between identity-first language and greater stigma ( 44 ), more recent findings suggest that it is the lack of an explicit diagnostic label, rather than the phrasing of the label, that elicits the greatest impact on stigma ( 45 , 46 ). In particular, vignettes of people with schizophrenia were associated with greater fear, anger, blame, and perceived danger when a diagnostic label was not provided, while these responses did not differ significantly when person-first and identity-first labels were used ( 46 ).…”
Section: Introductionmentioning
confidence: 91%
“…Other studies have shown that using person-first language to refer to individuals with MI results in higher levels of tolerance among professional counselors and community members (Granello & Gibbs, 2016;. These findings have also failed to replicate, suggesting that subtle differences in language may not impact stigmatizing attitudes about MI (Martinelli, 2020;Masland & Null, 2021;Nobel & Marson, 2016).…”
Section: Introductionmentioning
confidence: 99%